Composition-induced non-ergodic–ergodic transition and electrocaloric evolution in Pb1−1.5xLaxZr0.8Ti0.2O3 relaxor ferroelectric ceramics. Issue 4 (2019) - Li, Junjie; Yin, Ruowei; Su, Xiaopo; Li, Jianting; Qin, Shiqiang; Wei, Qiumei; Zhu, Mankang; Guo, Dong; Qiao, Lijie; Bai, Yang
No abstract available